The importance of corners in the tactical preparation of professional footballers - Lilic, A.; Stankovic, N.; Joksimovic, M.; Hadžovic, M.; Skrypchenko, I.; Mušovic, A. (European Journal of Physical Education and Sport Science, 2020)
Corners are a segment of the game from which goals are not often scored, but they may be a decisive factor in the outcome of the match between the two teams. The aim of this research is to determine the characteristics of performing a corner kick and to examine whether there are differences between different competitions of professional football players. The sample of respondents represents the matches of the International Champions Cup in the 2018 season and the matches of the Spanish league (La Liga) in the 2017/2018 season. A total of 23 matches (13 matches of the International Champions Cup and 10 matches of the Spanish league) were analyzed. To describe the tactics of corner kicks, variables were observed that indicate the way the kicks are performed from the corner. The methodology of observing several teams, monitoring all matches and monitoring both teams in each match with the analysis of given variables was used. Corner kicks that had more than three passes, which means starting a new, organized attack, were excluded from the analysis. A total of 209 of the 253 corners were included. The results show that there is no statistically significant difference in most of the observed parameters, but in the type of defense that the teams apply, play and lateral performance, there are statistically significant differences. Zone defense (.012) is used more by teams that competed in the International Champions Cup and combined (.036) by teams in the Spanish league. There are also differences in the playoffs (.047) in favor of the International Champions Cup. Corners from the same side (.031) were used more in the International Champions Cup than in the Spanish league. These results show that the teams do not differ much in the way they set up in the defensive phase and the attack phase, but that there are certain common criteria.